Communicative Competence in English Among Junior High School Students - Samaranos, Ann Jane; Biol Jr., Isidro (JPAIR Multidisciplinary Research, 2024)
Developing communicative competence is one of the expected outcomes of the Language Arts and Multiliteracies Curriculum (LAMC). This study evaluates the communicative competence among Junior High School students at Vinapor National High School. Employing descriptive quantitative and qualitative methods, it examines the grammatical, sociolinguistic, and discourse competence and identifies factors that either facilitate or hinder these competencies. A combination of grammatical, speaking, and writing tests was used to assess student’s performance, which revealed that the majority did not meet expectations across the evaluated competencies. Semi-structured interviews further provided insights into both facilitating and hindering factors from the perspectives of 21 students and four teachers. Facilitating factors included teaching methods, peer interaction, extracurricular activities, access to resources, and teacher support, whereas hindering factors encompassed challenges and barriers such as lack of interest, lack of comprehension, lack of confidence, fear of committing mistakes, negative perception, curriculum and resource limitations, and distractions. The study proposed an intervention program to guide teachers in helping students achieved communicative competence.
Keywords: Language skills; grammatical competence; socio-linguistic competence; discourse competence; motivating factors; hindering factors; enhancement program; descriptive; Philippines